Non-invasive Transdermal Delivery of Human Insulin Using Ionic Liquids: In vitro Studies - Jorge, Ludmilla R.; Harada, Liliam K.; Silva, Erica C.; Campos, Welida F.; Moreli, Fernanda C.; Shimamoto, Gustavo; Pereira, Jorge F. B.; Oliveira, José M.; Tubino, Matthieu; Vila, Marta M. D. C.; Balcão, Victor M. (Frontiers in Pharmacology, 2020)
In this research project, synthesis and characterization of ionic liquids and their subsequent utilization as facilitators of transdermal delivery of human insulin was pursued. Choline geranate and choline oleate ionic liquids (and their deep eutectic solvents) were produced and characterized by nuclear magnetic resonance (1H NMR), water content, oxidative stability, cytotoxicity and genotoxicity assays, and ability to promote transdermal protein permeation. The results gathered clearly suggest that all ionic liquids were able to promote/facilitate transdermal permeation of insulin, although to various extents. In particular, choline geranate 1:2 combined with its virtually nil cyto- and genotoxicity was chosen to be incorporated in a biopolymeric formulation making it a suitable facilitator aiming at transdermal delivery of insulin.